Respon Sosial Masyarakat Pesantren terhadap Tayangan “Xpose Uncensored” Trans 7: Analisis Sosiologi Pendidikan Islam” - Rosyidah, Titin; Huda, Muhammad Nurul; Arifin, Zainal (PT. Kreasi Karya Majakata, 2025)
This study examines the social response of the Islamic boarding school community to the Trans7 program Xpose Uncensored (October 13, 2025), which is considered to reduce the symbols of Islamic boarding schools, particularly the practice of ta'dhim and the moral position of kiai. Using a qualitative approach with content analysis of the broadcast and public responses on social media, this study utilizes three theoretical perspectives: Structural-Functional, Conflict, and Symbolic Interactionism. The results show that the pesantren community views this media representation as a threat to traditional values, the authority of kiai, and the identity of pesantren. The strong reactions that emerged functioned as a mechanism to maintain cultural integrity, reject media discourse domination, and preserve the symbolic meaning that has been institutionalized for generations. This study emphasizes the need for media representation ethics and cultural sensitivity in reporting on Islamic educational institutions.